Systematic Literature Review: Teknik Visualisasi Data Untuk Komunikasi Informasi Yang Efektif Di Berbagai Bidang - Satrio Adhiyatama Erlangga; Rr Nur Assifaa; Vitri Tundjungsari (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2026)
Data visualization (DV) has emerged as a vital mechanism for transforming complex data into comprehensible visual narratives. It has become an indispensable tool for effective information communication across various disciplines, including science, education, journalism, business, `healthcare, and public policy. This paper presents a Systematic Literature Review (SLR) analyzing 24 peer-reviewed publications sourced from Google Scholar (2015–2025). The synthesis indicates that well-designed visualizations, ranging from traditional charts to sophisticated interactive dashboards and narrative displays, significantly enhance user understanding, information retention, and interpretive accuracy. Nonetheless, challenges remain concerning cognitive overload, accessibility issues, and the lack of standardized measures for visualization literacy. The review introduces an integrative framework that categorizes visualization methods, tools, and contextual applications, providing insights and recommendations for future research aimed at advancing inclusivity, interpretability, and communicative efficacy across a variety of disciplines.